Islamic Students’ Perception on Essay Writing Challenges - Durratul Hikmah; Hayyin Maulina; Nabila Nabila (Universitas Nurul Jadid, 2022)
This study aims to find out the Islamic students’ perception of writing essay challenges. The sample of this research is 47 students majoring in English Education in one of the Pesantren-s in East Java. The research method used is descriptive quantitative with survey techniques. In this study, a questionnaire was used to determine the frequency of answers and the percentage. The data is calculated with Microsoft Excel. The main findings of this study are: there are 4 types of problems that students face in their essay writing course. They are confused in developing topics, grammatical errors, word choice problems, and poor organization. The overall mean of students' writing problems in the fourth semester is 3.35 and is categorized as